2008
DOI: 10.1111/j.1468-1331.2008.02099.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytidine‐5′‐diphosphocholine (Citicoline): a pilot study in patients with non‐arteritic ischaemic optic neuropathy

Abstract: Our results suggest a beneficial effect of oral Citicoline in NION.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 47 publications
2
35
0
6
Order By: Relevance
“…The choline deficiency could also be found in NAION patients, causing a deficiency of LysoPCs as products of choline; however, no significant differences of this molecule between patients and controls were found. Treatment with a precursor of choline, such as citicoline, has been used to improve consciousness levels in cerebral trauma and visual acuity in amblyopic patients (Fresina et al 2008) as well as to induce an improvement of the retinal and the visual pathway function in patients with glaucoma (Ottobelli et al 2013), although there are some controversial studies with regard to its efficiency (Davalos et al 2012;Parisi et al 2008).…”
Section: Metabolites As Potential Naion Biomarkersmentioning
confidence: 99%
“…The choline deficiency could also be found in NAION patients, causing a deficiency of LysoPCs as products of choline; however, no significant differences of this molecule between patients and controls were found. Treatment with a precursor of choline, such as citicoline, has been used to improve consciousness levels in cerebral trauma and visual acuity in amblyopic patients (Fresina et al 2008) as well as to induce an improvement of the retinal and the visual pathway function in patients with glaucoma (Ottobelli et al 2013), although there are some controversial studies with regard to its efficiency (Davalos et al 2012;Parisi et al 2008).…”
Section: Metabolites As Potential Naion Biomarkersmentioning
confidence: 99%
“…Potential neuromodulating and neuroprotective activity of citicoline has been effectively tried in patients with stroke [15], cognitive disorders [16,17] and Parkinson's disease [18,19,20]. In addition, a beneficial effect of citicoline has been described in a number of conditions affecting the visual system, like amblyopia [21,22,23,24] and nonarteritic ischemic optic neuropathy [25]. There are interesting findings concerning the use of citicoline in glaucoma [26,27,28,29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The results were evaluated through electrophysiological examinations, leading to a significant improvement in the patients. Thus, it has been found that CDP choline can be used to treat patients with optic neuropathy [64].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study of 26 patients with optic neuropathy-administered cytidine diphosphate (CDP)-choline for about 6 months showed that CDP-choline is effective in regenerating optic nerves in these patients [64].…”
Section: Nucleotids and Cobalamin And Their Application For Regenerationmentioning
confidence: 99%